2007
DOI: 10.1523/jneurosci.5129-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Enhances Visuospatial Attention by Deactivating Areas of the Resting Brain Default Network

Abstract: Nicotine-induced attentional enhancement is of potential therapeutic value. To investigate the precise attentional function(s) affected and their neuronal mechanisms, the current functional magnetic resonance imaging (fMRI) study used an attention task in which subjects responded to stimuli of high (INT high ) or low intensity presented randomly in one of four peripheral locations. Central cues of varying precision predicted the target location. In some trials, the cue was not followed by a target, allowing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
167
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 62 publications
27
167
3
2
Order By: Relevance
“…First, nicotine, a cholinergic agonist, was found to improve response latency in cue-target detection tasks by enhancing the cognitive brain mechanisms specifically involved in conditions where no extrinsic cue is provided [74,75]. Consistent with our results, the benefit in response latency was found to rely on the deactivation of the default activity of the dorsomedian frontal cortex, the precuneus and the PCC [75,76]. Second, the design used in this study was adapted from a classical task well known to engage the locus coeruleusnorepinephrine network [77][78][79][80].…”
Section: Relevance To the Neurochemical Bases Of Akinesiasupporting
confidence: 88%
“…First, nicotine, a cholinergic agonist, was found to improve response latency in cue-target detection tasks by enhancing the cognitive brain mechanisms specifically involved in conditions where no extrinsic cue is provided [74,75]. Consistent with our results, the benefit in response latency was found to rely on the deactivation of the default activity of the dorsomedian frontal cortex, the precuneus and the PCC [75,76]. Second, the design used in this study was adapted from a classical task well known to engage the locus coeruleusnorepinephrine network [77][78][79][80].…”
Section: Relevance To the Neurochemical Bases Of Akinesiasupporting
confidence: 88%
“…DMN deactivation has been linked to successful performance in cognitive tasks (Anticevic et al, 2010;Hahn et al, 2007), whereas failure of DMN deactivation during verbal WM has been observed in schizophrenia (Matsuo et al, 2013). Functional connectivity changes in DMN have also been reported in schizophrenia patients and their first-degree relatives (Garrity et al, 2007;Whitfield-Gabrieli et al, 2009).…”
Section: Limbic and Default Vmpfc And Their Relation To Performance Imentioning
confidence: 99%
“…In contrast, the control subjects deactivated some of these regions (PostCG5), consistent with similar deactivations during a large variety of other cognitive tasks as previously reported (Raichle ME et al, 2001). In general, task-related deactivations of brain regions have been associated with the temporary suspension of the baseline state (default mode) of brain function, and may be crucial for accurate performance on cognitive tasks (Hahn B, TJ et al, 2007;Raichle ME et al, 2001). Indeed, the inability to deactivate the PostCG in the cocaine subjects compared to control subjects may have contributed to the lower accuracy in the former group during the 2-back task.…”
Section: Hyperactivationmentioning
confidence: 99%